Impedance spectroscopy and transport mechanisms of TiO2-based dye sensitized solar cell - Farooq, W.A.; Atif, M.; Fatehmulla, A.; Yakuphanoğlu, Fahrettin; Yahia, I.S. (Virtual Institute of Physics of the Foundation Horia Hulubei, 2014)
Photoconduction mechanism and charge dynamics in the TiO2-based DSSC were analyzed under dark and illumination conditions. The effects of high and low electric fields on charge dynamics in the solar cell were investigated by current- voltage characteristics. It was found that the charge dynamics of the solar cell was controlled by the thermionic emission (TEC) at lower voltage and followed by space charge limited current (SCLC) at the higher voltages. It is also observed that photoconduction mechanism is controlled by supralinear recombination mechanism while the charge dynamics is controlled by TEC and SCLC mechanisms. Spectroscopic parameters (capacitance, conductance and series resistance) at different biasing voltages and frequencies are also discussed.
Keywords: Solar cell; Space charge limited current (SCLC); Spectroscopy; Thermionic emission (TEC)